The - Mills, C. Wright (Oxford University Press, 1999)
First published in 1956, The Power Elite stands as a contemporary classic of social science and social criticism. C. Wright Mills examines and critiques the organization of power in the United States, calling attention to three firmly interlocked prongs of power: the military, corporate, and political elite. The Power Elite can be read as a good account of what was taking place in America at the time it was written, but its underlying question of whether America is as democratic in practice as it is in theory continues to matter very much today